Analisis hubungan Rasio Trombosit Limfosit (RTL) dengan derajat keparahan stenosis pada pasien Coronary Artery Disease (CAD) - Zahra Inayah Kasim; Sulina Yanti Wibawa; Darmawaty E. Rauf (DiscoverSys Inc., 2019)
Background: Atherosclerosis in CAD is marked by formation of plaque inside the arterial lumen. Platelet plays a role on formation and development of atherosclerosis. Adhesion of platelets to the endothelial cells followed by releasing platelet granules caused inflammation of endothel. Lymphocytes also play a role in atherosclerosis and atherotrombosis. T lymphocyte was the first to be recruited inside atheromas and gathered along inside an unstable plaque. The severity of stenosis can be calculated using Gensini score. The Aim of this study is to analyze the correlation between PLR and degree of stenosis in CAD.Methods. This study is a retrospective study by collected 110 patients with CAD that had undergone coronary Angiography. Platelets and lymphocyte count were measured by automatic haematologycal analyzer. PLR was measured by dividing trombocyte count with absolute lymphocyte. Angiography findings were calculated using Gensini score and later devided into 3 groups according to degree of severity.Results. 110 patients retrospectively assesed, 80% were male and 20% female. The most age found was 50-59 years (35.5%). Using Anova test there is a significant differences onÂ PLR between 3 groups of lesions (p<0.05). Continued with Posthoc test, the only significant finding was PLR between moderate and severe lesion. By Spearmanâ€™s Correlation test, there is a positif colleration between PLR and severity of stenosis (p<0.048), with R value 0.189 (3.6%).Conclusions. There was a poor correlation between PLR and degree of stenosis severity in CAD. A prospective study needed to assess PLR as predictor of mortality and morbidity in CAD.